Formation of η-oriented shear bands and its significant impact on recrystallization texture in strip-cast electrical steel - Feng Fang; Jiale Wang; Jie Yang; Yuanxiang Zhang; Yang Wang; Guo Yuan; Xiaoming Zhang; R.D.K. Misra; Guodong Wang (Journal of Materials Research and Technology, 2022)
The evolution of shear band (SB) and texture in strip-cast electrical steel was studied in order to investigate the crystallographic character of SB and its influence on recrystallization texture. Shear deformation in the form of SB played an effective role in tailoring the local lattice rotation to accommodate heavy deformation in the case of inhomogeneous deformation under conditions of initial coarse grain in strip-cast electrical steel. During rolling process, η-oriented SBs appeared at different stages of deformation as a result of geometric softening. Cube-oriented SB was mainly retained from initial exact Cube grain at early stage of shear deformation and Goss-oriented SB was newly developed during the formation of γ-fiber matrix after heavy deformation. {210}<001> SB formed as a transition form among different SBs. Crystal rotation inside SB, SB dimension and SB boundary misorientation progressed in proportion to cold rolling reduction. It is demonstrated that crystallographic direction of SBs tended to be parallel to <001> under the driving force of reduction in stored energy to maintain relatively quasi-stable state. Low orientation gradient as well as relatively low density of dislocations was developed within SB region, while high orientation gradient formed between SB region and surrounding matrix. Interestingly, the η-oriented cell blocks inside SBs provided preferential nucleation sites for Goss and Cube texture at early stage of recrystallization, which significantly contributed to beneficial recrystallization texture in a manner of texture inheritance and superior magnetic properties (B50 was as high as 1.81 T, and P1.5/50 was as low as 4.0 W/kg).